The Role of Cooperatives for Trade, Industry, Mining, and Energy Office in Empowering SME - D. Dahliah (Golden Ratio of Marketing and Applied Psychology of Business, 2022)
The objectives of this study are: Firstly, to find out the factors driving and inhibiting the empowerment of SMEs in the Bulukumba district. Secondly, to find out the role of the Department of Cooperatives, SMEs, Trade, industry, mining, and energy in empowering MSEs in the Bulukumba district. The methodology used and the results obtained in this study are the author uses an experimental research method with an inductive approach. The results of this study are: 1). creating a conducive climate, 2). increasing financing and capital for SMEs, and 3). targets for increasing cooperation for all business actors, both private and government. From this observation, it is suggested that the empowerment of micro, small, and medium enterprises in the Bulukumba Regency is carried out by the Bulukumba Regency government, and the Bulukumba Regency Government can embrace micro, small and medium business actors in Bulukumba Regency to promote small-capitalized businesses jointly. As conclusion, the government needs to cooperate with other agencies such as banks so that they can get capital quickly for SME actors, which are still very difficult to reach, which can encourage and increase SMEs. So, government can advance funds in implementing SME empowerment programs and to increase the income.